COMPETE BY «HIRCH’S»? - Dmitry A. Novikov (Высшее образование в России, 2016)
The paper analyzes in a polemical form the typical aberrations and myths (common as for officials from science governance, and, often, for the scientists) about the possibility and expediency of using formal bibliometric indicators to assess the working efficiency of individual and collective research activities.